Video Game Addiction in Young People (8-18 Years Old) after the COVID-19 Pandemic: The Grey Area of Addiction and the Phenomenon of "Gaming Non-Pathological Abuse (GNPA)" - Domenico Piccininno; Giulio Perrotta (MDPI AG, 2024)
Introduction: In the literature, video game addiction in youths is correlated with dysfunctional symptoms of anxiety, emotional disorders, and mood disorders, and the pandemic period of 2020-2022 has favored the aggravation of this behavioral addiction. Therefore, we identified the need to analyze this phenomenon with an emphasis on the risks and correlates related to deviance and maladjustment from a prospective perspective, seeking to understand the impact of the individual variables examined. Aim: To demonstrate whether the condition of "gaming non-pathological abuse" (GNPA) promotes psychopathological features of clinical interest, in the absence of a diagnosis of "gaming disorder" (GD). Materials and methods: A search performed on PubMed and administration of an ad hoc sociological questionnaire were used to investigate individual variables of criminological interest in a representative population sample (531 males/females, 8-18 years old, M: 14.4, SD: 2.5). Results: Statistical analysis showed that after the pandemic period, digital video game addiction was reinforced, feeding psychopathological traits consistent with anxiety, emotional disorders, and mood disorders. Variables correlated with impulsive, aggressive, and violent behavior related to age, gender, socio-environmental and economic background, and the severity of digital video game addiction. Conclusions: In the youth population (8-18 years), "gaming non-pathological abuse" (GNPA) is related to aggressive, impulsive and violent behaviors that foster phenomena of social maladjustment and deviance, especially in individuals living in disadvantaged or otherwise complex socio-economic and family contexts. Looking forward, the study of structural and functional personality profiles is essential in order to anticipate and reduce the future risk of psychopathological and criminal behavior.